2018
DOI: 10.12795/revistafuentes.2018.v20.i2.03
|View full text |Cite
|
Sign up to set email alerts
|

Políticas educativas para el apoyo de trayectorias escolares en el nivel medio en América Latina: la provisión de recursos como estrategia

Abstract: Despite the significant progress made in the extension of educational systems in Latin America and in particular with regard to the average level, the persistence of societies marked by inequality in which the Right to Education remains a promise for many children and teenagers. The object of study of the research presented in this article has been the educational policies that are developed with impact on secondary schools in Latin America that work in contexts of social vulnerability in order to improve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
1
0
2
Order By: Relevance
“…A review of the impact of garden-based learning on academic outcomes revealed consistent positive results across programs, students samples, and school types (Williams and Dixon, 2013). Interestingly, gardens are also useful tools to engage students with food production and help reflect on production and consumption models (Llerena and Espinet, 2017;Pineda Encalada and Estrada Martínez, 2019), and promote healthy eating habits (Berezowitz et al, 2015;Davis et al, 2015;Ohly et al, 2016). They moreover allow students gaining outdoor experiences, which is valuable since a growing body of empirical evidence exists on the fact that outdoor classrooms increase wellbeing and boost subsequent classroom engagement (Kuo et al, 2018;Largo-Wight et al, 2018), and on the impacts of greening schoolyards on children's health and wellbeing (Kelz et al, 2013;Van Dijk-Wesselius et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the impact of garden-based learning on academic outcomes revealed consistent positive results across programs, students samples, and school types (Williams and Dixon, 2013). Interestingly, gardens are also useful tools to engage students with food production and help reflect on production and consumption models (Llerena and Espinet, 2017;Pineda Encalada and Estrada Martínez, 2019), and promote healthy eating habits (Berezowitz et al, 2015;Davis et al, 2015;Ohly et al, 2016). They moreover allow students gaining outdoor experiences, which is valuable since a growing body of empirical evidence exists on the fact that outdoor classrooms increase wellbeing and boost subsequent classroom engagement (Kuo et al, 2018;Largo-Wight et al, 2018), and on the impacts of greening schoolyards on children's health and wellbeing (Kelz et al, 2013;Van Dijk-Wesselius et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Con proximidad teórica y metodológica al conjunto anterior, distinguimos una serie de trabajos que ubicamos en el enfoque de la microsociología política (GARCÍA, 2018(GARCÍA, , 2020KRICHESKY, 2014;BARRERA, 2018;TERIGI et al, 2013;VIEGO, 2015). Este enfoque se caracteriza por su abordaje en la escala micro (local-institucional) de la acción e interacción social, considerando la influencia y los condicionamientos del entorno o las estructuras sociales.…”
Section: Enfoques Teóricos Y Metodológicosunclassified
“…Ahora bien, al margen de esta coincidencia, los artículos difieren entre sí tanto por sus pretensiones como por sus recursos y logros en el análisis de esta agenda y de sus interacciones con otras escalas. Por una parte Revista de Estudios Teóricos y Epistemológicos en Política Educativa, v. 8, e21646, p. 1-15, 2023 Disponible en: <https://revistas2.uepg.br/index.php/retepe> 7 encontramos textos que reconocen la agenda supranacional como contexto, sin analizarla ni indagar sobre los procesos de formación de políticas en su interacción multiescalar (ESPER, 2017;GARCÍA, 2018GARCÍA, , 2020RÍOS;FERNÁNDEZ, 2015). En otro caso (SVERDLICK, 2019) encontramos una mayor profundidad en la consideración de la agenda, entendida como campo discursivo y espacio de disputa política por los sentidos en términos de hegemonía.…”
Section: Haciendo Foco En El Abordaje De La Dimensión Supranacionalunclassified